Comparison of pancreatic volume and fat amount linked with glucose homeostasis between healthy Caucasians and Koreans. Issue 11 (16th July 2018) - Roh, Eun; Kim, Kyoung M.; Park, Kyeong S.; Kim, Yoon J.; Chun, Eun J.; Choi, Sung H.; Park, Kyong S.; Jang, Hak C.; Lim, Soo
Abstract : Aim: To compare pancreatic volume and fat amount, and their associations with glucose homeostasis, in a Korean and a white population. Materials and methods: In 43 healthy Korean and 43 healthy white people, matched for age (±3 years) and body mass index (BMI; ±1 kg/m 2 ), we measured pancreatic volume and fat amount in the pancreas and abdomen using computed tomography. Pancreatic β‐cell function and insulin resistance were estimated according to biochemical characteristics and a 75‐g oral glucose tolerance test. Body composition and resting energy expenditure (REE) were examined using bioimpedance and indirect calorimetry, respectively. Results: The mean ±SD age of the participants was 29.9 ± 5.9 years and 30.0 ± 5.2 years, and BMI was 24.0 ±3.7 and 24.1 ±3.2 kg/m 2 in the white participants and the Korean participants, respectively. Pancreatic volume in the white participants was greater than that in Korean participants (77.8 ±11.6 vs 68.2 ±12.1 cm 3 ; P  < .001). Pancreatic fat content in Korean participants was 22.8% higher than in white participants ( P  = .051). Insulinogenic index, disposition index, muscle mass and REE were significantly lower in Korean participants. Pancreatic volume was positively associated with indices linked to β‐cell function; fat content in the pancreas was negatively associated with such indices, and positively with insulin resistance after adjusting for relevant variables including REE. Conclusions: A smaller pancreas and higher fat deposition might be crucial determinants of vulnerability to diabetes in Korean people compared with white people with similar BMI and body fat levels.